RADIATION-INDUCED INSTABILITY OF THE HUMAN GENOME DURING LOW-DOSE IRRADIATION - Domina, Emiliia (European Science, 2024)
The problem of radiation-induced carcinogenesis has become particularly relevant due to the distant negative consequences of the Chernobyl disaster. According to modern ideas, the genome instability of irradiated persons plays a determining role in initia